2018
DOI: 10.3389/fpubh.2018.00176
|View full text |Cite
|
Sign up to set email alerts
|

Self-Control in Intertemporal Choice and Mediterranean Dietary Pattern

Abstract: Background: The Mediterranean Diet (hereinafter MD) is considered a healthy dietary pattern. Adherence to this pattern can be assessed by means of the KIDMED test by which individuals are assigned an index and classified into three groups of adherence to MD: high, medium, and low. In addition, impulsivity or impatience in intertemporal choice has been defined as a strong preference for small immediate rewards over large delayed ones.Objective: This study examines the relationship between dietary habits, specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…This paper completes Muñoz Torrecillas et al (1) results and conclusions investigating the relationship between adherence to healthy dietary habits, specifically the Mediterranean Diet (hereinafter, MD), and impulsivity in intertemporal choices. Impulsivity can be defined as the strong preference for small immediate payoffs over larger delayed payoffs, and in the original study this behavior was captured by the parameter k (discount rate of the hyperbolic discount function), calculated using an automated scoring mechanism.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…This paper completes Muñoz Torrecillas et al (1) results and conclusions investigating the relationship between adherence to healthy dietary habits, specifically the Mediterranean Diet (hereinafter, MD), and impulsivity in intertemporal choices. Impulsivity can be defined as the strong preference for small immediate payoffs over larger delayed payoffs, and in the original study this behavior was captured by the parameter k (discount rate of the hyperbolic discount function), calculated using an automated scoring mechanism.…”
supporting
confidence: 83%
“…Muñoz Torrecillas et al (1) observed that participants in the highest diet adherence group exhibited the lowest impulsivity, and participants in the lowest diet adherence group displayed the greatest impulsivity (see Figure 1; larger k -values represent greater impulsivity), but these differences were not statistically analyzed. Therefore, the purpose of the present paper is to quantitatively model the relationship between dietary adherence and impulsivity, and put forth preliminary evidence regarding its nature.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Increasingly, these models have been used as measurement tools, whereby parameter estimates are interpreted as indices of latent components of the choice process. For example, estimates of the discount rate parameter of the hyperbolic and exponential models, which reflects the rate at which future outcomes are discounted, is often used as a measure of impulsiveness (e.g., Kirby, Petry, & Bickel, 1999;Muñoz Torrecillas et al, 2018). Differences in discount rate parameter estimates have been explored between people of different age groups (Samanez-Larkin et al, 2011), clinical populations (Cheng & González-Vallejo, 2014), and across a variety of experimental manipulations (Haushofer et al, 2013;Li et al, 2018;S.…”
mentioning
confidence: 99%